2022
DOI: 10.1177/03080226221107772
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for returning to work after traumatic injury: A public and professional involvement study

Abstract: Introduction Following traumatic injury, occupational therapists (OTs) are pivotal in supporting people to return-to-work (RTW) and regain independence. Aim: to identify priorities for RTW after traumatic injury and highlight barriers hindering the process. Method We recruited 17 participants with direct (i.e. trauma survivor [ n = 11]; OT trauma survivor [ n = 2]) or indirect (i.e. OT [ n = 4]) experience of returning to work following traumatic injury. Online consultations, lasting 60 min, were guided by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…For example, a recent study in the UK reported on the importance of resuming work after injury for enhancing survivors' sense of purpose in life, nurturing self-identity and encouraging social interaction. 40 The current study reflects a slightly lower return-to-work success rate (59%) than the other two studies in Ethiopia. Tamene and colleagues reported in 2022 that 73.5% of participants returned to work 45 days after the injury, 24 while in an earlier study, researchers found that 83% had returned to their preinjury work 6 months after the injury was reported.…”
Section: Implications For Participation and Economic Activitycontrasting
confidence: 57%
“…For example, a recent study in the UK reported on the importance of resuming work after injury for enhancing survivors' sense of purpose in life, nurturing self-identity and encouraging social interaction. 40 The current study reflects a slightly lower return-to-work success rate (59%) than the other two studies in Ethiopia. Tamene and colleagues reported in 2022 that 73.5% of participants returned to work 45 days after the injury, 24 while in an earlier study, researchers found that 83% had returned to their preinjury work 6 months after the injury was reported.…”
Section: Implications For Participation and Economic Activitycontrasting
confidence: 57%